2009
DOI: 10.1111/j.1365-3059.2008.02017.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of control of two soilborne pathogens following incorporation of above‐ and below‐ground residues of Brassica juncea into soil

Abstract: The persistence of control of primary infections caused by two soilborne fungal plant pathogens, Rhizoctonia solani and Gaeumannomyces graminis var. tritici , following the incorporation of above-ground parts (AP), below-ground parts (BP) or both (AP + BP) of Brassica juncea into soil was examined through an experiment in controlled conditions. Control was quantified by measuring disease incidence in bioassays where inoculum was introduced at different dates after the incorporation of plant residues. All types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…The biological effects of GSLs and GHPs have been known since the early 1990s, when several authors investigated their effects on the growth and development of bacteria (19,23), insects (24)(25)(26), fungi (27,28), and nematodes (29,30), and our knowledge about the deterrent or attractant effects of the main glucosinolates on different pests (generalists and specialists) and parasitoids is well documented. Other authors have tested the effects of GHPs and GSLs on soil pathogens by incorporating Brassica residues into soil or by testing their effect by using in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effects of GSLs and GHPs have been known since the early 1990s, when several authors investigated their effects on the growth and development of bacteria (19,23), insects (24)(25)(26), fungi (27,28), and nematodes (29,30), and our knowledge about the deterrent or attractant effects of the main glucosinolates on different pests (generalists and specialists) and parasitoids is well documented. Other authors have tested the effects of GHPs and GSLs on soil pathogens by incorporating Brassica residues into soil or by testing their effect by using in vitro assays.…”
Section: Discussionmentioning
confidence: 99%
“…Bending and Lincoln (17) demonstrated the toxic properties of crucifer tissues after their incorporation into soil, which limits the growth of weeds, fungus, and nematodes. GHPs have a positive effect in reducing soil pathogens, but their persistence varies depending on the compound (17)(18)(19). Brader et al (20) reported that the accumulation of GSLs in Arabidopsis thaliana L. enhanced resistance to Erwinia carotovora (Jones) and P. syringae pv.…”
mentioning
confidence: 99%
“…In the case of Brassica juncea it has been shown that the above-and belowground plant components produce different isothiocyanates, which show different persistence once the plant residues have been incorporated in the soil (Kirkegaard and Sarwar 1998). Motisi et al (2009) described the non-additive effect of the incorporation of leaves and /or roots of B. juncea against Rhizoctonia solani and Gaeumannomyces graminis var. tritici and suggested the existence of a complex interaction between these two type of residues.…”
Section: Introductionmentioning
confidence: 99%
“…tritici and suggested the existence of a complex interaction between these two type of residues. The toxicity of isothiocyanates or other glucosinolates-related compounds to various microorganisms has been well documented (Gamliel 2000;Bailey and Lazarovits 2003;Mazzola and Cohen 2005, Manici et al 2000, PiedraBuena et al 2006, Mattner et al 2008Motisi et al 2009). Chemicals of this group such as methylisothiocyanate, the active ingredient of metham sodium and dazomet, are widely used as soil fumigants.…”
Section: Introductionmentioning
confidence: 99%
“…Although the generation of biologically active ITC continues to be described as the dominant means by which diseases are suppressed in response to Brassica soil amendments, an emerging body of evidence indicates alternative modes of action (Mazzola et al 2001;Mattner et al 2008;Motisi et al 2009), certain of which are biologically mediated (Cohen et al 2005;Cohen and Mazzola 2006;Mazzola et al 2007). Brassica tissue particle size has potential to affect disease control efficacy as this will influence spatial dispersal of these materials through the soil profile.…”
Section: Introductionmentioning
confidence: 99%